Value at risk of the exchange rate in southeast ASEAN-3 based on bayesian Markov-switching GARCH approach - Mingyang Li (2020)
© Published under licence by IOP Publishing Ltd. This study analyzes Bayesian Markov-Switching of the single regime and the two regimes to forecast the risk of the exchange rate in three ASEAN countries, and various GARCH family and distribution are selected by DIC to find the best fitting models. This study will help governments to prevent the recurrence of events like the 1997 financial crisis. The study finds that Thailand has the best exchange rate stability and the lowest risk and is most suitable for foreign investors seeking stability.